Novel advances in biotransformation and bioactivation research—2019 year in review. (2nd July 2020) - Khojasteh, S. Cyrus; Driscoll, James P.; Jackson, Klarissa D.; Miller, Grover P.; Mitra, Kaushik; Rietjens, Ivonne M. C. M; Zhang, Donglu
Abstract: Biotransformation is one of the main mechanisms used by the body to eliminate drugs. As drug molecules become more complicated, the involvement of drug metabolizing enzymes increases beyond those that are typically studied, such as the cytochrome P450 enzymes. In this review, we try to capture the many outstanding articles that were published in the past year in the field of biotransformation (see Table 1 ). We have divided the articles into two categories of (1) metabolites and drug metabolizing enzymes, and (2) bioactivation and safety.  This annual review is the fifth of its kind since 2016 (Baillie et al. 2016 ; Khojasteh et al. 2017, 2018, 2019 ). This effort in itself also continues to evolve. We have followed the same format we used in previous years in terms of the selection of articles and the authoring of each section. I am pleased of the continued support of Rietjens, Miller, Zhang, Driscoll and Mitra to this review. We would like to welcome Klarissa D. Jackson as a new author for this year's issue. We strive to maintain a balance of authors from academic and industry settings.  We would be pleased to hear your opinions of our commentary, and we extend an invitation to anyone who would like to contribute to a future edition of this review. Cyrus Khojasteh, on behalf of the authors.